(untitled) (Development Service Industry Management, 2023)
The article analyzes the current state of cruise tourism in the world and outlines the opportunities and prospects for the development of cruise tourism in Ukraine. The theoretical and methodological foundations of cruise tourism were studied, the concept of cruise tourism was defined, and the history of the development of cruises in the world and in Ukraine, in particular, was highlighted. The question of types of cruises, and peculiarities of the technology of organizing cruises in the world are considered, the objects and subjects of the industry are defined, and the conditions for the development of this type of tourism are described in detail. The peculiarities of the organization of cruise tourism are determined. The trends and problems of the development of cruise tourism under the prism of the world and Ukrainian tourism industry are highlighted. Statistical information on the types, duration of cruises, the total number of cruise tourists, as well as added data on revenues from the cruise tourism direction, are provided. The cruise routes of Ukraine are analyzed, and a SWOT analysis of obstacles to the development of this type of tourism in Ukraine is also presented. An analysis of the activities of cruise companies represented on the domestic market, namely the companies "Royal Caribbean International" and "Inflotcruises", was carried out. The impact and consequences of the COVID-19 pandemic on the state of the industry were studied, market coverage by the largest cruise companies was analyzed, and data on cases of infection with COVID-19 on international cruise ships were provided. Statistical data on the change in profits of the world’s leading companies engaged in cruise services were analyzed, as well as the change in the total liabilities of these enterprises was studied. The prospects for the development of cruise tourism in the world and Ukrainian markets are analyzed, in particular, in the post-war period using the example of the experience of such "sea" countries as Croatia, Cyprus, Egypt, and Israel, which became popular with tourists after the war, and their numerous water resources are actively used for the development of sea and river cruise tourism. To popularize cruise tourism in Ukraine after our victory, a one-day cruise tourist product "Cruise trip on the mighty Dnieper" was developed. Recommendations for the development of cruise tourism in Ukraine in the post-war period are described. Forecasts of the development of world cruise tourism until 2030 have been analyzed.